Finite sequent calculi for PLTL - Alonderis, Romas; Pliuškevičius, Regimantas; Pliuškevičienė, Aida (Lietuvos matematikos rinkinys, 2015)
Two sequent calculi for temporal logic of knowledge are presented: one containing invariant-like rule and the other containing looping axioms. Its proved that the calculi are equivalent, sound and complete.
Keywords: temporal logic of knowledge; theorem proving; sequent calculus; invariant rule; looping axioms